ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PEGAWAI DINAS KOPERASI, USAHA KECIL DAN MENENGAH DI KABUPATEN OGAN KOMERING ULU TIMUR - Dyah Ayu Putriani; Titie Syahnaz Natalia; Andri Irawan; Dahlia Dahlia (Jurnal Bisnis Darmajaya, 2023)
This study discusses the analysis of the factors that influence the performance of employees of the cooperative, small and medium enterprises in East Ogan Komering Ulu Regency. The data analysis technique used is multiple linear regression. The data used uses primary data. The results showed that partially analysis has a significant influence on the performance of employees of the union, Small and Medium Enterprises Office, meaning that the workload has a significant influence on the performance of the employees of the union, Small and Medium Enterprises Office. The results showed that simultaneously all independent variables Analysis (X1) and Workload (X2) jointly have a significant influence on the performance of the union Office employees, Small and Medium Enterprises. The job analysis variable (X1) and the workload variable (X2) are strategic factors for improving the performance of cooperative, small and medium enterprise employees, this is because the results of this study have a significant effect. This research is expected to be useful for the cooperative, small and medium enterprises in East Ogan Komering Ulu Regency in making decisions regarding employee performance issues. The research is expected to be useful in further research as a reference and to be able to develop more apart from these variables for example (competence, work motivation, empowerment of human resources, job satisfaction and others)Keywords: Job Analysis, Workload, Employees’ Performance